A Comprehensive Study on Diabetic Foot Ulcer & its Management - Sharma, Puneet (International Research Journal of Ayurveda & Yoga, 2022)
A devastating side effect of diabetes, diabetic foot exacerbates the patient’s health and has a big socioeconomic impact. The current review aims to describe the pathogenetic mechanisms and causes of diabetic foot while concentrating on its management as a significant health concern. Along with good foot care, raising doctors’ awareness and, consequently, their capacity to recognize the "foot at risk" may lower the likelihood of amputation by preventing diabetic foot ulcers.